Pengembangan E-Modul Berbasis Stem pada Materi Genetika - Putri Apriani Pasaribu; Miza Nina Adlini (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aims to develop stem-based e-modules on genetic material in an effort to improve the quality of biology learning. The research method used is Research and Development (R&D) with a 4D development model. The results showed that the stem-based e-module in genetics had gone through the validation process by material experts and media experts, with the percentage of validity and materials of 95%, the ability and contextualization of 87.5%, and a score of 100% for appearance and programming and 97.2% for presentation from media experts. This e-module is considered very practical based on the assessment of teachers and students in small and large-scale trials, with a percentage of practicality of 94.23% for the teacher, 76.538% for small scale students, and 78.32% for large scale students. The implementation of e-modules in biological learning is also proven to be quite effective, with a percentage of effectiveness of 58.46% and the N-Gain value of 0.58, which is included in the medium category. The conclusion is that the development of stem-based e-modules in genetic material is an effective innovation in improving the quality of biology learning, providing interactive learning experiences, encouraging students to be more active in the learning process, and increasing students' understanding of genetic material. Keywords: E-Modules, Genetics, Stem, 4D